Effect of nitrogen levels on yield, root biomass distribution, nitrogen recovery by forage grasses and changes in soil properties of acid Inceptisol - SINGH, K A (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted for 5 years to study the effect of fertilizer N on the productivity of 3 forage grassesand changes in the soil properties of an acid InceptiSol at an altitude of 1 250 m in Sikkim. Dallis grass (Paspalumdilatatum Poiret) and 'BN 82048' hybrid pearlmillet [Pennisetum glaucum (L.) R. Br.emend Stuntz] x napier grass (P.purpureum Schum) gave highest dry-matter at 150 kgN/ha and para grass [Brachiaria mutica (Forsska) Stapf] at 50 kgN/ha over 5 years but the response to Ndecreased with the age of the grasses. With increase in N level dry-matter producedproduced /kg of N increased but the crude protein cOntein and N recovery decreased except former 2 parameters in paragrass. Maximum root biomass was at 50 kg N/ha. With application of N, root distribution in 0-20 cm soil depth increasedwith corresponding decrease in 20--6O cm soil depth. Soil pH, organic carbon, available phosphorus and potassiumincreased and exchangeable aluminium, calcium and magnesium cations decreased over 5 years. N application tended todecrease soil pH, organic carbon, available phosphorus and exchangeable calcium and magnesium cations and increasedexchangeable aluminium